Additions and corrections to Wolf Leslau's Comparative Dictionary of Ge'ez (1987–2017) - Kogan, Leonid (JAOS, 2019)
Thirty years after the appearance of Wolf Leslau's Comparative Dictionary of Geʿez, the present study aims at correcting and updating some of the entries of this major tool of Semitic etymology. New data from Ugaritic, Akkadian, and especially Modern South Arabian are prominent among the additions (particularly the Soqotri lexical material acquired in the course of the many years of the author's fieldwork on the island).